2022
DOI: 10.3389/fphar.2022.873030
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of N6-Methyladenosine RNA Methylation as Regulators in Cancer Therapy and Drug Resistance

Abstract: N6-methyladenosine (m6A) RNA methylation has been considered the most prevalent, abundant, and conserved internal transcriptional modification throughout the eukaryotic mRNAs. Typically, m6A RNA methylation is catalyzed by the RNA methyltransferases (writers), is removed by its demethylases (erasers), and interacts with m6A-binding proteins (readers). Accumulating evidence shows that abnormal changes in the m6A levels of these regulators are increasingly associated with human tumorigenesis and drug resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 186 publications
(190 reference statements)
0
12
0
Order By: Relevance
“…These epitransciptomic changes were shown to promote EBV infection in vitro [38,39]. Furthermore, accumulating evidence demonstrated that abnormal changes in the m 6 A levels are associated with human tumorigenesis and drug resistance [40][41][42].…”
Section: Global Dna Methylation Levels Allow the Discrimination Betwe...mentioning
confidence: 98%
“…These epitransciptomic changes were shown to promote EBV infection in vitro [38,39]. Furthermore, accumulating evidence demonstrated that abnormal changes in the m 6 A levels are associated with human tumorigenesis and drug resistance [40][41][42].…”
Section: Global Dna Methylation Levels Allow the Discrimination Betwe...mentioning
confidence: 98%
“…Abnormal RNA modifications have been detected in a variety of diseases [ 24 , 33 , 34 ]. In particular, studies showed that RNA modification dysregulations could play important roles in cancer initiation, metastasis, prognosis, and responses to therapies [ 23 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Mechanistically, RNA modifications could affect the expression of genes involved in important oncogenic pathways such as the Wnt/β-catenin pathway, the PI3K-Akt-mTOR pathway, the JAK-STAT pathway, the MAPK pathway, the p53 pathway, the Hippo Pathway, etc.…”
Section: Epitranscriptomicsmentioning
confidence: 99%
“…Base modifications in mRNA, such as adenosine to inosine deamination (A-to-I editing), N6-methyladenosine (m 6 A) modification and cytosine to uracil deamination, play pivotal roles in various types of biological and pathological processes [ 1 ]. A-to-I editing and m 6 A modification are two of the most common RNA modifications controlling gene expression in mammals, and they have emerged as hot topics in cancer research [ 2 , 3 ]. A-to-I RNA editing is carried out by the adenosine deaminases acting on RNAs (ADARs: ADAR1/2) through conversion of adenosine to inosine within cellular RNA in mammals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%